Polycyclic aromatic hydrocarbons in firefighters : attitudes, deposition and decontamination of proximity firefighting protective clothing - Arouca, Aline Marcelino (2023)
Tese (doutorado) — Universidade de Brasília, Instituto de Química, Programa de Pós-Graduação em Química, 2023.